TINJAUAN SOSIOLOGIS PROGRAM PEMBERDAYAAN DISABILITAS NETRA DI YAYASAN DRIYA RABA (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
The limitations of persons with disabilities, especially those with visual disabilities, which are the highest variety of disabilities in Bali, do not prevent them from getting empowerment. This study analyzes sociologically the strategies and challenges and constraints of the blind disability empowerment program at the Driya Raba Foundation, Bali Province. Community Development Theory by Jim Ife and Frank Teseriero is a scalpel in analyzing the empowerment of blind people in foundations. Qualitative methods are used in this study with descriptive research types. The results of this study indicate that the Driya Raba Foundation provides an empowerment program in the form of providing ethics education and the main skills, namely music and massege. Empowerment of interests and talents apart from primary education is also given, such as in the field of sports. The foundation is a place for people with visual disabilities to get empowerment as capital to survive in the future. Social challenges such as the behavior of persons with disabilities in foundations, economic constraints in meeting operational costs are the core problems in the empowerment program at Driya Raba. The results of the study also show the creation of various positive impacts for people with visual disabilities which can be seen from the success, achievements and independence of alumni in carrying out and dealing with the realities of living together with normal people after completing the empowerment program at the Driya Raba Foundation. Key words: Driya Raba, Empowerment, Challenges, Constraints, Visual Disabilities